Optimal Cutoff Levels of More Sensitive Cardiac Troponin Assays for the Early Diagnosis of Myocardial Infarction in Patients With Renal Dysfunction. Issue 23 (9th June 2015) - Twerenbold, Raphael; Wildi, Karin; Jaeger, Cedric; Gimenez, Maria Rubini; Reiter, Miriam; Reichlin, Tobias; Walukiewicz, Astrid; Gugala, Mathias; Krivoshei, Lian; Marti, Nadine; Moreno Weidmann, Zoraida; Hillinger, Petra; et al.
Abstract : Background—: It is unknown whether more sensitive cardiac troponin (cTn) assays maintain their clinical utility in patients with renal dysfunction. Moreover, their optimal cutoff levels in this vulnerable patient population have not previously been defined. Methods and Results—: In this multicenter study, we examined the clinical utility of 7 more sensitive cTn assays (3 sensitive and 4 high-sensitivity cTn assays) in patients presenting with symptoms suggestive of acute myocardial infarction. Among 2813 unselected patients, 447 (16%) had renal dysfunction (defined as Modification of Diet in Renal Disease–estimated glomerular filtration rate <60 mL·min −1 ·1.73 m −2 ). The final diagnosis was centrally adjudicated by 2 independent cardiologists using all available information, including coronary angiography and serial levels of high-sensitivity cTnT. Acute myocardial infarction was the final diagnosis in 36% of all patients with renal dysfunction. Among patients with renal dysfunction and elevated baseline cTn levels (≥99th percentile), acute myocardial infarction was the most common diagnosis for all assays (range, 45%–80%). In patients with renal dysfunction, diagnostic accuracy at presentation, quantified by the area under the receiver-operator characteristic curve, was 0.87 to 0.89 with no significant differences between the 7 more sensitive cTn assays and further increased to 0.91 to 0.95 at 3 hours. Overall, the area under the receiver-operator characteristic curve in patients with renal dysfunction was only slightly lower than in patients with normal renal function. The optimal receiver-operator characteristic curve–derived cTn cutoff levels in patients with renal dysfunction were significantly higher compared with those in patients with normal renal function (factor, 1.9–3.4). Conclusions—: More sensitive cTn assays maintain high diagnostic accuracy in patients with renal dysfunction. To ensure the best possible clinical use, assay-specific optimal cutoff levels, which are higher in patients with renal dysfunction, should be considered. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00470587. Abstract : Supplemental Digital Content is available in the text.